Patient-Centered Outcomes After Modified Vestibulectomy. Issue 5 (May 2020) - Das, Deepanjana; Davidson, Emily R. W.; Walters, Mark; Farrell, Ruth M.; Ferrando, Cecile A.
Abstract : (Abstracted from Obstet Gynecol 2020;135:113–121) Vulvodynia is a complex gynecologic pain condition characterized by at least 3 months of vulvar pain with no identifiable cause. Symptoms can be categorized as generalized vulvodynia (with unprovoked pain affecting the entire vulvar) or as provoked vestibulodynia (with localized pain at the vestibule).